Fluid substitution, dispersion, and attenuation in fractured and porous reservoirs - Insights from new rock physics models - Gurevich, Boris; Galvin, Robert; Brajanovski, Miroslav; Mueller, Tobias; Lambert, Gracjan (Society of Exploration Geophysicists, 2007)
The importance of natural fractures for development and production of hydrocarbon reservoirs requires little justification. While in clastic reservoirs fractures can cause permeability anisotropy and thus affect field development, in carbonates and tight sands they are often critical for reservoir production. If open fractures have a preferential direction (which is almost always the case), they cause azimuthal seismic anisotropy, making seismic a powerful tool for the characterization of fractured reservoirs.